2017
DOI: 10.1080/19415257.2016.1274268
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of early career teachers: new initiatives and old problems

Abstract: The task of supporting beginning teachers has received considerable attention in recent years, and numerous initiatives have been implemented. In this paper we investigate the experiences of early career teachers (ECTs) in New South Wales, Australia, at a time when their employing authority mandated the provision of mentors and reduction in face-to-face teaching for ECTs. This paper draws on ECTs' responses to survey items asking about their experiences as ECTs. It emerged that many of the issues of the early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 30 publications
1
29
0
3
Order By: Relevance
“…These factors continue to feature in the more recent literature (e.g. Meister & Melnick, ; Liston et al ., ; Dicke et al ., ; Schuck et al ., ). A number of studies have also identified working with children with special needs as a particular challenge for new teachers (Meister & Melnick, ; Fantilli & McDougall, ; Anthony et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…These factors continue to feature in the more recent literature (e.g. Meister & Melnick, ; Liston et al ., ; Dicke et al ., ; Schuck et al ., ). A number of studies have also identified working with children with special needs as a particular challenge for new teachers (Meister & Melnick, ; Fantilli & McDougall, ; Anthony et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Novice teachers can receive support by building healthy relationships with their experienced colleagues. This will facilitate their familiarization with the profession (Schuck et al, 2018). In addition, it has been pointed out that teaching performance is parallel to effective relationship and communication with students and mentoring and coaching process will guide inexperienced teachers how to be better communicators.…”
Section: Discussionmentioning
confidence: 99%
“…Både ledelse, kolleger og foreldre har alle sine normative interesser, og organisasjonen de nyutdannede kommer inn i er allerede preget av etablerte verdier, relasjoner og strategier. Skolen kan utvikle visse strategier for å imøtekomme nye laerere, strategier som støtter dem i den grad de tilbys en jobb tilpasset dem, det tilrettelegges for samarbeid mellom laerere og det gis ekstra støtte til nytilsatte (Johnson, 2006;Kraft, Marinell, & ShenWei Yee, 2016;Schuck, Aubusson, Buchanan, Varadharajan, & Burke, 2018). Kelchtermans og Ballet (2002) anbefaler på bakgrunn av sin studie at det de kaller «micropolitical literacy» (s.118) bør få en systematisk start allerede i laererutdanning, saerlig knyttet til praksisopplaering, for deretter å følges opp som en del av introduksjonsordnin gen for nye laerere.…”
Section: Empirisk Forskningunclassified